2001
DOI: 10.7748/ns2001.04.15.32.33.c3017
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine in rural care part 1: developing and evaluating a nurse-led initiative

Abstract: All involved in the nurse-led telemedicine service viewed it favourably and patients said that they would use it again. Part two, to be published in next week's Nursing Standard, will discuss the findings of the evaluation in relation to the wider picture of nursing involvement in teleconsultation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…Consistent with Mair and Whitten, 4 this review also found that average percentages of patients defined as "satisfied" (usually on the basis of agreement with positively worded statements) are generally greater than 80%, and researchers frequently report 100% satisfaction with their service. 19,20,25,36,39,47,48,71,74,78,84,85,100,107 These findings are also consistent with the patient satisfaction literature for standard medical care, which reveals that patients tend to give high ratings of satisfaction with their healthcare. 11,13,16,111 However, these findings must be interpreted cautiously for several reasons: Given that patient satisfaction measurement is unavoidably tied to service delivery, it is difficult to disentangle the extent to which satisfaction data reflects "real" healthcare evaluation and that which is influenced by the healthcare setting.…”
Section: Patient Satisfaction Measurementsupporting
confidence: 89%
“…Consistent with Mair and Whitten, 4 this review also found that average percentages of patients defined as "satisfied" (usually on the basis of agreement with positively worded statements) are generally greater than 80%, and researchers frequently report 100% satisfaction with their service. 19,20,25,36,39,47,48,71,74,78,84,85,100,107 These findings are also consistent with the patient satisfaction literature for standard medical care, which reveals that patients tend to give high ratings of satisfaction with their healthcare. 11,13,16,111 However, these findings must be interpreted cautiously for several reasons: Given that patient satisfaction measurement is unavoidably tied to service delivery, it is difficult to disentangle the extent to which satisfaction data reflects "real" healthcare evaluation and that which is influenced by the healthcare setting.…”
Section: Patient Satisfaction Measurementsupporting
confidence: 89%
“…The patients were satisfied with its convenience and appreciated the nurses’ role in explaining points that they had not understood during the consultation. Additionally, the numbers of patients treated solely by the community health nurse increased significantly, while fewer patients needed referral to a physician (Macduff, West, & Harvey, 2001). Another study compared APNs using telemedicine in three rural Missouri counties with APNs who did not utilize telemedicine.…”
Section: Telemedicine In Advanced Nursing Practicementioning
confidence: 99%
“…These two different meanings of technology have been mentioned in the material despite the experiences of technical problems, difficulties, and demands for knowledge and skills required by the use of technology. In general, technology was perceived as positive [24][25][26][27][28][29][30][31][32][33][34].…”
Section: Resultsmentioning
confidence: 99%